(untitled) (Scientific journal of the Fergana State University, 2026)
This article explores the essence, goals, and principles of governance as an integral part of human development from ancient times to the present day. It analyzes the political views of past rulers, the evolving concepts of justice and equality across centuries, and the role and importance of people’s interests in governance. The study also highlights the evaluations of political figures and thinkers of earlier periods, as well as the reflections and conclusions of kings, illustrated through examples drawn from authentic historical sources.